Nickel catalyzed C-N coupling of haloarenes with B2N4 reagents - Qianqian Chang; Qini Li; Yi-Hui Deng; Tian-Yu Sun; Yun-Dong Wu; Leifeng Wang (Nature Communications)
Abstract Carbon-heteroatom bond (especially for C-N bond) formation through nickel catalysis has seen significant development. Well-established Ni(0)/Ni(II) redox cycle and photoinduced Ni(I)/Ni(III) redox cycle have been the dominant mechanisms. We report a thermally driven Ni-catalyzed method for C-N bond formation between haloarenes and B2N4 reagents, yielding N,N-dialkylaniline derivatives in good to excellent yields with broad functional group tolerance under base-free conditions. The catalytic protocol is useful for base-sensitive structures and late-stage modifications of complex molecules. Detailed mechanistic studies and density functional theory (DFT) calculations indicate that a Ni(I)/Ni(III) redox cycle is preferred in the C-N coupling process, and B2N4 reagent serves both as a single electron transfer donor and a N,N-dialkylation source.